2023
DOI: 10.1027/1864-9335/a000500
|View full text |Cite
|
Sign up to set email alerts
|

Populist Attitudes Predict Compliance-Related Attitudes and Behaviors During the COVID-19 Pandemic Via Trust in Institutions

Abstract: Abstract. While previous research discussed populism as a phenomenon of declining trust, we investigated the predictive value of populist attitudes for citizens’ trust, attitudes, and behaviors during the COVID-19 pandemic. Moreover, we tested the role of trust in several institutions simultaneously. As preregistered, the cross-sectional ( N = 1,090) and longitudinal ( n = 216) data collected (April to June, 2020) in Germany ( n = 617) and Poland ( n = 473) showed that stronger populist attitudes predicted hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…The analysis of correlations in our study showed that populist attitudes are positively correlated with conspiracy beliefs about COVID-19, age (older participants are more populist), right-wing political orientation, and negatively correlated with trust in government institutions, perception of the spread of the virus, concern about COVID-19, acceptance of anti-COVID-19 vaccines, and compliance with anti-COVID-19 measures. These results are consistent with those found in the literature (e.g., Ehrke et al, 2023;Recio-Román et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
“…The analysis of correlations in our study showed that populist attitudes are positively correlated with conspiracy beliefs about COVID-19, age (older participants are more populist), right-wing political orientation, and negatively correlated with trust in government institutions, perception of the spread of the virus, concern about COVID-19, acceptance of anti-COVID-19 vaccines, and compliance with anti-COVID-19 measures. These results are consistent with those found in the literature (e.g., Ehrke et al, 2023;Recio-Román et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
“…Taken together, Hechler et al' (2023) findings illustrate the importance of social defense strategies, in particular, to facilitate understanding others even during a crisis. Ehrke et al (2023) extend previous work on populism and investigate the relationship between populist attitudes, trust in several institutions (media, politics, science), and COVID-19-related compliance attitudes as well as behaviors. Cross-sectional and longitudinal data from 2020 in Germany and Poland suggest that populist attitudes are linked to trust in alternative media but lack of trust in mainstream media, politics, and science.…”
mentioning
confidence: 68%
“…Particularly trust in political and scientific institutions seems to be relevant for compliance. Ehrke et al' (2023) findings thereby highlight social-cognitive processes such as trust that may underly the detrimental consequences of populist attitudes during a health crisis. Mullins et al (2023) examined the extent to which parental understanding of Latina children's distress predicted children's affective empathy and prosocial behavior during the COVID-19 pandemic.…”
mentioning
confidence: 81%
“…These group-based appraisals lead to experiencing group-based emotion, such as trust and social satisfaction. A lot of research has found a positive relationship between trust and compliance behaviors (Burton et al, 2023; Ehrke et al, 2023; Lalot et al, 2023; Miao et al, 2023; Ridenhour et al, 2022; Rudert et al, 2021; Scandurra et al, 2023; Shi et al, 2021).…”
Section: A Social Perspective: the Social Identity Theory And Othersmentioning
confidence: 99%